The nutrition and feeding of farmed fish and shrimp - a training manual - Tacon, Albert G.J. (FAO, 1987)
The principles of feed and fertilizer analysis are described and the chemical composition of various potential feed ingredients and fertilizers presented; including the cereal grains and by products,...